DESKRIPSI MOTIVASI BELAJAR FISIKA SISWA KELAS X MIA DI SMAN 9 KOTA JAMBI - Sitompul, Ratna Sari; Astalini, Astalini; Alrizal, Alrizal (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2018)
The purpose of this research is to describe the learning motivation of physics students of class X MIA in SMAN 9 Kota Jambi. The type of this research is descriptive research with quantitative approach. The population of this study is the students of class X MIA in SMAN 9 Kota Jambi. The sampling technique in this research is total sampling. The research instrument used is questionnaire motivation learn physics student. The data type of this research is quantitative data. Data analysis technique used is quantitative analysis using descriptive statistics. The results of this study indicate that the learning motivation of physics students of class X MIA in SMAN 9 Kota Jambi on intrinsic motivation dimension derived from the diligent indicators in doing the task that tends to be in the high category with the percentage of 59.80% where student attitudes are in the category often and on dimensions extrinsic motivation stems from indicators of feedback that tend to be in the high category with a percentage of 61.76% where student attitudes are in the category often. Keywords: description, learning motivation, physics